Building an evidence engine to promote more responsive government. - Munteanu, Ioana; Newcomer, Kathryn E.; Best, Clifton (Public Administration Review)
Public agencies require timely and reliable evidence to adapt operations and strategies quickly to effectively tackle unanticipated challenges in service to the American people. Federal agencies are generally not well equipped to take full advantage of the resources they own to effectively align with evidence needs. Guidance has been issued to fill this gap, yet federal agencies have not fully adopted the use of evidence, especially performance data, in decision‐making. Moreover, both law and academia provide little guidance on how agencies can connect the demand and supply of knowledge. This paper discusses how the Federal Acquisition Service (FAS) of the General Services Administration (GSA) has developed and sustained a framework for collecting and transforming data into reliable evidence to inform decision‐making, that is, created an evidence engine. Federal agencies can learn from the FAS approach to improve their evidence‐building activities to achieve economies of scale, reduce costs, and increase evidence‐informed responsiveness to ever‐changing needs.